CAREGIVER EMPOWERMENT AS AN EFFORT TO CREATE SEMADU ELDERLY - Retno Indarwati; Elida Ulfiana; Eka Misbahatul Mar'ah Has; Chandra Rahmadi; Laila Mufida; Yulia Yunara; Vera Veriyallia; Silvia Farhanidiah (Universitas Airlangga, 2023)
Introduction: The world is experiencing a drastic rise in the number of elderly, both in absolute terms and as a percentage, due to the aging population. Nearly half of Indonesia's old people in 2021 suffer physical and mental health issues. The significance of the caregiver's role in helping the elderly fulfill their fundamental requirements and daily activities. This community service's goal is to offer caregivers the tools they need to raise elderly persons who are healthy, independent, and productive. Methods: This community service is conducted through providing elderly caregivers instruction and training. 25 elderly caregivers participated in this community service. Three stages of implementation are included in this community service's activities: dementia, Activity Daily Life (ADL) with fall risk information, and creativity training. Results: It has been found that the Sig.2-tailed value is 0.000 which means it is less than the p value <0.05, so there is a significant difference in the results of knowledge about dementia in the pretest and post-test data. The cadres looked enthusiastic in following the given training. The benefit of the training of creativity for the elderly is to train memory, prevent dementia, and keep the elderly active in old age. Conclusion: There is a significant increase on the evaluation of knowledge about dementia Empowering health cadres can improve the quality of life and health status of the elderly. Elderly caregivers here are health cadres. Through this community service, it can become a solution and effort in dealing with the aging population in Indonesia.